Local adaptation of Geoffroy's horseshoe bat, Rhinolophus clivosus, to the Cape floristic region of South Africa - Walker, Maryalice Harkins (University of Cape Town, 2014)
Includes bibliographical references (leaves 77-90). === Populations of species adapt to the environment in which they live. This study investigated local adaptation in Rhinolophus clivosus (Chiroptera: Rhinolophidae) by comparing its phenotype with that of a co-occurring endemic species. R. capensis, in the Cape Floristic Region of South Africa. If R. clivosus has become locally adapted, its phenotype would be predicted to have diverged from R. clivosus populations elsewhere in the country while converging upon R. capensis. Evidence for local adaptation was found in R. c/imslls at De Hoop Nature Reserve. The population has undergone a reduction in body size with correlated allometric responses in flight morphology. The wing shape of R. clivosus at De Hoop has not changed, resulting in a reduction in wing loading with a consequent increase in manoeuvrability. Thus R. clivosus at De Hoop is simply a scaled-down version of R. clivosus elsewhere and a scaled-up version of R. capensis. Factors such as competition and gene flow may have mitigated against local adaptation, however. Furthermore. whether phenotypic plasticity rather than natural selection may have been responsible for the apparent convergence between R. capensis and R. clivosus requires future research and advances in the study of evolutionary development and population genetics.